Implementasi Program MBKM dalam Kurikulum Program Studi Pendidikan Bahasa dan Sastra Indonesia, Universitas Palangka Raya - Nirena Ade Christy (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The implementation of the MBKM program in the Indonesian Language and Literature Education Study Program (PBSI), Department of Language and Arts Education (JPBS), Teaching and Education Faculty FKIP), Palangka Raya University (UPR) was carried out as an effort so that this program could be adapted to the needs of the Study Program curriculum. . Therefore, a supporting Curriculum for MBKM and MBKM Guidelines for the PBSI, FKIP, UPR Study Programs were prepared which contained a number of provisions related to MBKM. One of these provisions is the equalization of courses in the curriculum with the MBKM program so it is necessary to know the input of the courses to be implemented in the MBKM program. This study uses a qualitative method through a literature study approach (library research) on sources from books, articles, and regulations that discuss the impact of the MBKM program on the equivalence of courses in the curriculum. The results of this study are that the Indonesian Language and Literature Education Study Program at Palangka Raya University has two activities carried out to support the study program competencies, namely Intra-Curricular and Co-Curricular activities in the implementation of the MBKM Program. Intra-curricular activities, namely (a) lectures in the same study program outside the University of Palangka Raya, and (b) lectures in different study programs inside and or outside the University of Palangka Raya. Meanwhile, the implementation of the MBKM Program Co-Curricular Activities supports the competence of study programs and is implemented through the MBKM program with several forms of activities, such as student exchanges, internships/work practices, teaching assistantships, research/research, humanitarian projects, entrepreneurial activities, independent studies/projects. , and building real thematic work villages/colleges. Implementation of the MBKM Program Co-curricular activities in the curriculum can be carried out in semesters 4-7 with a total of 88 credits earned.